EFFECT OF HYDROSTATIC PRESSURE ON THERMODYNAMIC PROPERTIES OF NiTi SHAPE MEMORY ALLOY - Tatar, C.; Yildirim, Z.; Kaygili, O. (Polska Akad Nauk, Polish Acad Sciences, Inst Metall & Mater Sci Pas, 2017)
The effect of hydrostatic pressure and different heating/cooling rates on physical properties and microstructure of NiTi shape memory alloy has been investigated. The transformation temperatures and physical properties of the alloy have changed with applied pressure. It has been clearly seen from Differential Scanning Calorimetry (DSC) that with the increase of applied pressure, while A(s) and A(f), and M-f transformation temperatures decrease, M-s value increase. Moreover, based on the increase of the pressure amount applied on the sample, there was an average increase of 48% for Gibbs free energy and 18% for elastic strain energy. Entropy of the alloys decreases depending on the increase in the amount of applied pressure for all heating rates. Depending on the amount of applied pressure on the sample, an interior strain of 0.177% at most was observed. With the increase of applied pressure on the sample, it was determined that activation energy increased. Additionally, the Scanning Electron Microscopy (SEM) images of the samples show that the grain sizes of the unpressured sample and the samples on which pressure is applied are between 40 and 120 mu m, which was determined by Image Analysis Method.
Keywords: Shape Memory Alloy; Phase Transformation; Differential Scanning Calorimetry; Electron Microscopy; Gibbs Free Energy; Activation Energy